Dizer a verdade sob todos os riscos: parrhesia by Carlos Marighella in a speech on National Radio - Mazzola, Renan (2022)
Based on the discussions on parrhesia found in A coragem da verdade, Michel Foucault's last course taught at the Collège de France in 1984, this paper intends to: a) present the definition and functioning of parrhesia in Greek Antiquity; b) point out the developments of parrhesia in modernity; c) analyze the exercise of parrhesia in the speech of Carlos Marighella broadcast on Rádio Nacional, in the context of the Brazilian Military Dictatorship. This research is affiliated to the field of Foucauldian discursive studies, and analyzes six enunciative sequences of the corpus by the archegenealogical perspective of Michel Foucault. We demonstrate that Marighella's pronouncement is configured as an aleturgical modality, introducing risks to those who assume its authorship and inscribing themselves in the parrhesiastic game.